Pragmatismo e Humanitarismo: a política externa brasileira e a causa armênia (1912-1922) - Loureiro, Heitor de Andrade Carvalho [UNESP] (2016)
In the 1910s, Brazilian audience heard, for the first time, about the ‘Armenian Cause’ through the work of the intellectual Etienne Brasil. At that time, Brasil published several articles through the press and scientific societies in Rio de Janeiro, in which he portrayed the Armenians as Christian people from the East which had suffered all types of persecutions by the hands of the Turk-Muslims within the Ottoman Empire. Brasil’s reports were Orientalist in nature, largely spread in western thought at the time as a way of appealing to the Brazilian readership and decision-makers in order to support Armenians to create the Armenian Republic. When Armenia became independent, in 1918, Etienne Brasil became the first Armenian diplomatic representative in South America, which provided him an opportunity to address his appeals to the Brazilian presidency and to the Minister of External Relations in search of support to sustain the fragile republic whose population was majority composed by refugees, and survivors of the genocide perpetrated by the Ottoman government after 1915. This research aims to examine how the “Armenian cause” – range of juridical demands of the Armenian people within the international system – arrived in Brazil and became part of the Brazilian foreign policy agenda. Armenian demands were incorporated on this policy agenda by a small interest group that had been able to obtain access to decision-makers through personal connections and intensive press propaganda. Brazil was trying to realign itself within the international system as a key player after the Great War. In this context, the Armenian cause was presented by Etienne Brasil as an opportunity to show to the Powers that Brazil was ready to deal with challenges in that new global scenario and, therefore, deserved the prominent place that it had received at the Paris Peace Conference in 1919 and at the League of Nations. The hypothesis is that Brazilian support towards the Armenian Cause was a Pessoa administration’s pragmatic act that sought, through a humanitarian agenda, to gain prestige at the global level. However, this did not happen proactively. The Brazilian government responded to the pressure of this group of Armenians living in Rio de Janeiro and the American moves at the international arena. As such, this group worked as part of a diaspora acting as a transnational power, which could take advantage of the Brazilian political system’s porosity to influence Brazil’s agenda. The methodology consisted in analyzing files and documents from archives in Brazil and abroad to reconstitute the negotiations between Armenians and Brazilians in order to get the latter to support the former at the international fora, as well as analyzing the Rio de Janeiro’s press in the 1910-20s, which were a tool to sensitize public opinion to push Brazil to take action. In the late 1920, the Brazilian government finally accepted to act as mediator in the conflict between Armenians and Turks imbued with the modern humanitarianism ideas, but guided by the pragmatism and desire for prestige in the international system.